KEPEMIMPINAN, KOMITMEN, DAN BUDAYA ORGANISASI MEMPENGARUHI KINERJA KARYAWAN (Studi Kasus: PT.SUMRE1CON DI KOTA BALIKPAPAN - Ariani, Misna Ariani (Fakultas Ekonomi Universitas Balikpapan, 2018)
Abstract  A good company or organization, will focus human resources, because it is expected to perform its function optimally, especially facing the dynamics of environmental changes that occur. Some successful companies or organizations have a leader who can manage and create effective and efficient human resources. This study aims to prove and analyze the influence of Leadership, Commitment, and Organizational Culture on Employee Performance PT.Sumre1con in Balikpapan City. The analysis tools used are Multiple Linear Regression Test and Classic Assumption Test, Validity Test and Reliability Test. In the multiple linear regression equation analysis, independent variables including Leadership (X1), Commitment (X2), Organization Culture (X3) together have a significant influence on Employee Performance (Y) PT.Sumre1con in Balikpapan City. This is evidenced by the magnitude of R square, R, and F-count> F-table. And leadership variables have a dominant influence on employee performance PT.Sumre1con in the city of Balikpapan, with t-count> t-table and at a significant level α and the largest partial r-value from the other.